SEQUENCE OF SELECTED QUALITY MANAGEMENT TOOLS TO ANALYZE QUALITIVE PROBLEMS OF PRODUCTS - Dominika SIWIEC; Martin STRAKA; Andrzej PACANA (Modern Management Review, 2023)
Identification of causes of incompatibilities of the products treated with the powder method allows their elimination or minimization of those differences, which contributes to the improvement of the powder coating method and thus to the development of processes in the field of metallurgy. The aim of the article is to analyze the corrosion problem on the ventilator cover with the use of the sequence of selected quality management instruments (Ishikawa diagram and the 5Why method) and proposed actions to eliminate or minimize the problem and improve the powder coating process and organization within the workplace place of the selected company. The analysis was carried out at the request of the management of the Podkarpackie fan producer. The management wanted to analyze some of a problems in the simple and cheaper way, and thus in the enterprise this using the types of the method was not practiced. The management were wanted to analyze the problem with using these types of method because, in this enterprise, this was not practiced yet. The analysis of corrosion using the new sequence – Ishikawa diagram and 5Why method allowed, i.e.: appropriate analysis of the problem, identified the root cause of adequate problem and proposed the actions for the problem, thanks to which is possible to improve the powder coating process and a good organization workplace in the selected company. The sequence used and the proposed improvement actions can be used to analyze quality problems in other production and service companies.